Czy zasada „sola Scriptura”pomaga czy przeszkadza w zjednoczeniu chrześcijaństwa? - Dariusz Kazimierz Bartoszewicz (Warszawskie Studia Teologiczne)
The principle of sola Scriptura is one of the four rules of the Reformation movement. Its meaning, however, is not precisely determined. Protestants consider the Bible the only source of Revelation. This is not only a source of knowledge but also source of faith. Contemporary hermeneutics was initiated by Protestant philosophers and theologians. But nowadays it has been accepted and is also being developed by the Catholic theologian. The greatest novelty introduced by the Reformation is not a methodological modification at the noematic level but a difference in the perception of oneself as an interpreting person. The Reformation gave the individual the courage to undermine the rules accepted by the community. The personal activity on the community was put to the fore, and the community's action on the individual was limited to the necessary minimum. It seems that the slogan sola Scriptura is just an invitation to individualism in interpretation. The principle that puts the Bible directly in the center of community life requires interpretation as every word. It seems that a common agreement on the understanding of this principle by Catholics and Protestants, in which the role of the community in the process of interpretation would be recognized, could open a new chapter in the pursuit of the reunification of Christianity.